Reduction of briquette composite made of low grade from ore and biomass ash - Yunus, Nurul Azhani; Ani, Mohd Hanafi; Purwanto, Hadi; Mohd. Salleh, Hamzah; Zamani Abd Rashid, Rusila; Akiyama, Tomohiro (South East Asia Iron and Steel Institute, 2012)
Mini blast furnace project has been constructed to increase pig iron production for domestic consumption produced by HyL process. Malaysia has no significant high grade iron ore deposit white domestic low grade ore could not utilized for direct reduction process. Beneficiation of the low grade ore containing crystalline water from Malaysian iron ore deposits is an attractive alternative resource for domestic iron-making. However, the use of tow grade iron ore in iron making requires extra energy consumption and contributes to greenhouse gases. we proposed a series of processes for beneficiation of local iron ore utilizing renewable and environmental friendly agricultural residues from domestic palm oil industry as an energy source and processing materials. Briquette composites of iron ore and ash by product of palm oil empty Fruit Bunch (EFB) pyrolysis were produced with minute amount of water added as binder. Reduction tests were carried out between 600'c to 900.c under argon atmosphere in a glass tube furnace. The extent of sample reduction was estimated by oxygen removal and considering the weight toss. The chemical and structural changes of iron ore before and after reduction were characterized using XRD, TG/DTA and SEM. The results showed that increase in reduction temperature and EFB ash content in the briquette will increase the extent of reduction. XRD results suggest that the original iron oxide hydrate in the ore has been converted into hematite after heating at desired temperature due to dehydration process. Hematite was partiality reduced to magnetite and wustite after reduction and the extent of reduction increased with increasing ash content. The results also indicate that ash from EFB could be a promising energy source for upgrading low grade iron ore by producing reducing gas that will replace part of coal in iron making leading to reduction in CO emission.